Pengaruh Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa dengan Akuntabilitas Sebagai Variabel Mediasi - Ayem, Sri; Kusumasari, Kirana Feby (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aims to determine the effect of internal control systems for fraud with accountability as a mediation variable.This study took samples in Ngaglik and Ngemplak sub-districts. Data collection is done directly by using questionnaires. The population in this study is the head of the village or PJ Kadus, the financial section of financial vows or financial staff and some of the Secretary and General Staff. From the survey spread obtained 30 samples. The data analysis techniques in this study used double linear regression techniques and the moderated regression analysis with the help of SPSS (Statistic Package for Social Science) program version 18.0. The results showed that the government internal control system was influential about accountability while the government's internal control system had no effect on Fraud and the government's internal control system had no effect on fraud with accountability as a mediation variable.